1994
DOI: 10.1007/bf00357569
|View full text |Cite
|
Sign up to set email alerts
|

Ensilage of tropical grasses mixed with legumes and molasses

Abstract: The effects of adding two legumes, Gliricidia sepium and Leucaena leucocephala, cv. Cunningham, and molasses on the fermentation characteristics of silages made from two tropical grasses (Pangola grass, Digitaria decumbens, and Setaria sphacelata cv. Kazungula) were investigated. Pangola grass silages contained significantly higher contents of water-soluble carbohydrates and lactic acid than did setaria silages after 100 days fermentation, but there were no significant differences between the two silages in po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
5
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 4 publications
2
5
0
Order By: Relevance
“…Molasses addition increased the residual water soluble carbohydrate (WSC) contents (12 v. 20 g/kg DM for silages without and with molasses, respectively), and in setaria silages also significantly reduced the NH 3 -N contents of the silages (56 v. 37 g/kg TN for silages without and with molasses, respectively). These effects were consistent with the findings of a previous experiment in laboratory silos (Tjandraatmadja et al 1993). However, as seen from Table 2, silages without molasses were already well preserved.…”
Section: Effects Of Molasses and Legume Addition On Silage Qualitysupporting
confidence: 92%
See 1 more Smart Citation
“…Molasses addition increased the residual water soluble carbohydrate (WSC) contents (12 v. 20 g/kg DM for silages without and with molasses, respectively), and in setaria silages also significantly reduced the NH 3 -N contents of the silages (56 v. 37 g/kg TN for silages without and with molasses, respectively). These effects were consistent with the findings of a previous experiment in laboratory silos (Tjandraatmadja et al 1993). However, as seen from Table 2, silages without molasses were already well preserved.…”
Section: Effects Of Molasses and Legume Addition On Silage Qualitysupporting
confidence: 92%
“…However, difficult in the hot, wet conditions in which they grow where anaerobic conditions are maintained, tropical and silages made from tropical species have been forages ensiled at high temperatures (> 30 °C) can produce silages of high lactic acid but low protein content (Tjandraatmadja et al 1991). Tjandraatmadja et al (1993) have also shown that silages made from mature tropical grasses (pangola grass and setaria) were improved by the addition of leaves from the tree legumes Leucaena leucocephala or Gliricidia sepium, producing silages of low pH (3-8-4-4) and ammonia content and high total N (TN) content (> 20 g N/kg DM). The following experiment investigates the effects of inclusion of molasses (as a fermentation aid) and tree legume leaves in silages from two tropical grasses on the nutritive value of these silages for sheep.…”
Section: Introductionmentioning
confidence: 99%
“…Our results reinforce the benefits that grass silages obtain with the inclusion of gliricidia, such as improvement of the fermentation process, reduction of NDF, and increases in the DM digestibility, reported in previous studies (Tjandraatmadja et al, 1994;Kato et al, 2006;Oduguwa et al, 2013).…”
Section: Discussionsupporting
confidence: 92%
“…However, in some regions, particularly in tropical countries, gliricidia has been used during ensiling, and after wilting, because this legume can improve fermentation in silages (Tjandraatmadja et al, 1993a,b;Cabral Jr. et al, 2007). The quality of corn, pangola grass, and setaria silage is improved by the addition of gliricidia (Tjandraatmadja et al, 1994;Kato et al, 2006), presumably leading to superior animal performance (Costa et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the rapid establishment and consequent maintenance of anaerobic conditions throughout ensiling is essential for LAB proliferation. For silages made from temperate grasses, LAB levels of at least 3·9 log cfu g −1 are desirable for a good fermentation process but lower values have been reported as normal in silages from tropical grasses (Tjandraatmadja et al. , 1994a,b; Pedroso et al.…”
Section: Discussionmentioning
confidence: 99%